Farmers’ rights and access and benefit sharing mechanisms in community seed banks in Nepal - Gauchan, D.; Joshi, B.K.; Bhandari, B. (2018)
Farmers’ Rights and access and benefit sharing (ABS) are important and interlinked issues in the conservation and sustainable use of agrobiodiversity. This chapter aims to assess the current status and policy gaps of implementing farmers’ rights and ABS mechanisms with regard to community seed banks and the conservation and sustainable use of agrobiodiversity in Nepal. It also explores potential options and strategies to promote community seed banks as local legitimate institutions for formalizing ABS mechanisms and realizing farmers’ rights. The information for this study is generated and synthesized from a review of relevant policies and programs, key informant interviews and focus group discussions with community seed bank members and stakeholder consultation meetings. Recently, community seed banks (CSBs) are emerging as important communitybased institutions for local level access and exchange of genetic resources, strengthening local seed system, realizing farmers’ rights and safeguarding agrobiodiversity. They are also gradually emerging as a local grass-roots institution for crop improvement, variety maintenance and registration of local varieties for increased benefit sharing with farmers and local communities. A well-functioning CSB adopts community biodiversity management (CBM) approaches and tools, such as community biodiversity register, diversity field school, diversity fair, community biodiversity management fund, participatory plant breeding, value addition and marketing to promote local access, exchange, use and conserve crop genetic resources using customary rules and practices. At present, however, there are no formal mechanisms, rules, guidelines and protocols for facilitating access, exchange and use of genetic resources from the CSBs in line with national and international policies and protocols. Considering this situation, we propose a model for developing a community seed bank as a legitimate institution (platform) for prior-informed consent (PIC) and ABS mechanisms and formalizing farmers’ rights to genetic resources. This will, however, require creating incentive mechanisms for custodian farmers and communities and bringing support from formal sector agencies through relevant policies, legislation and programs to promote and sustain community seed banks.